2021
DOI: 10.34067/kid.0003512021
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Immune Response to SARS-CoV-2 Vaccination in Dialysis Patients and in Kidney Transplant Recipients

Abstract: Background: Kidney failure patients on dialysis or after renal transplantation have a high risk for severe COVID-19 infection and vaccination against SARS-CoV-2 is the only expedient prophylaxis. Generally, immune responses are attenuated in kidney failure patients, however, systematic analyses of immune responses to SARS-CoV-2 vaccination in dialysis patients and in kidney transplant recipients (KTR) are still missing. Methods: In this prospective multicentric cohort study, antibody responses COVID-19 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 31 publications
(64 reference statements)
1
34
0
Order By: Relevance
“…Korh et al and Danthu et al reported anti-SARS-CoV-2 IgG seroprevalence rates of 22% (5/23) and 4.1% (3/74), respectively, in KT recipients, based on the LIAISON® SARS-CoV-2 Trimetric-S IgG assay (Diasorin, Italy) with a positive cutoff value of 13.0 arbitrary units/mL 3 , 7 . Kolb et al reported a seroprevalence of 37% (10/28) using the Anti-SARS-CoV-2 QuantiVac ELISA for spike protein (Euroimmun, Germany) with a positive cutoff value of 35.2 binding antibody units/mL 6 . Benomane et al and Bertrand et al reported seroprevalence rates of 40.3% (64/159) and 17.8% (8/45 recipients), respectively, using the ARCHITECT ® IgG II Quant test for spike protein (Abbott Laboratories) with a positive cutoff value of 50.0 arbitrary units/mL 2 , 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Korh et al and Danthu et al reported anti-SARS-CoV-2 IgG seroprevalence rates of 22% (5/23) and 4.1% (3/74), respectively, in KT recipients, based on the LIAISON® SARS-CoV-2 Trimetric-S IgG assay (Diasorin, Italy) with a positive cutoff value of 13.0 arbitrary units/mL 3 , 7 . Kolb et al reported a seroprevalence of 37% (10/28) using the Anti-SARS-CoV-2 QuantiVac ELISA for spike protein (Euroimmun, Germany) with a positive cutoff value of 35.2 binding antibody units/mL 6 . Benomane et al and Bertrand et al reported seroprevalence rates of 40.3% (64/159) and 17.8% (8/45 recipients), respectively, using the ARCHITECT ® IgG II Quant test for spike protein (Abbott Laboratories) with a positive cutoff value of 50.0 arbitrary units/mL 2 , 5 .…”
Section: Discussionmentioning
confidence: 99%
“… 8 Twenty‐eight of the 225 KTRs were included in a previously published study. 9 All participants had to be older than 18 years, with no history of previous COVID‐19 and able to give informed consent to participate in the study. All KTRs were on stable immunosuppressive medication.…”
Section: Methodsmentioning
confidence: 99%
“…Shortly, the previously described control group was composed of volunteers from a nursing home, who had no history of kidney failure 8 . Twenty‐eight of the 225 KTRs were included in a previously published study 9 . All participants had to be older than 18 years, with no history of previous COVID‐19 and able to give informed consent to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, as of 7th January 2022, 137 different COVID-19 vaccines are in various phases of clinical trials, while 194 are in the preclinical phase; emergency-use approved vaccines are recommended prioritizing people with chronic diseases, with certain clinical conditions and old age [ 8 ]. Studies have reported that vaccines show weak immunogenicity among kidney transplant recipients as they do not produce antibodies effectively [ 9 , 10 ]. Moreover, live or replication component vaccines are contraindicated in transplant recipients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%